2021
DOI: 10.1097/rct.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Magnetic Resonance Imaging for International Federation of Gynecology and Obstetrics 2018 IB to IIB Cervical Cancer Staging: Comparison Among Magnetic Resonance Sequences and Pathologies

Abstract: Objective: This study aimed to investigate the most accurate magnetic resonance (MR) sequence for tumor detection, maximal tumor diameter, and parametrial invasion compared with histopathologic diagnoses.Methods: Fifty-one patients with International Federation of Gynecology and Obstetrics 2018 IB1 to IIB cervical cancer underwent preoperative MR imaging and surgical resection. Two radiologists independently evaluated the tumor detection, parametrial invasion, and tumor size in each of T2-weighted image, diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Ran et al’s [ 22 ] MRI findings were evaluated by a radiologist with 7 years’ experience in pelvic MRI diagnosis and a senior radiologist with 20 years’ experience in pelvic MRI diagnosis. For Matsumoto et al [ 23 ], all the MR examinations were interpreted independently by 2 board-certified radiologists with 24 years and 11 years of experience in gynecologic cancer imaging. For Rockall et al [ 25 ], all the imaging scans were read by one local and two central radiologists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ran et al’s [ 22 ] MRI findings were evaluated by a radiologist with 7 years’ experience in pelvic MRI diagnosis and a senior radiologist with 20 years’ experience in pelvic MRI diagnosis. For Matsumoto et al [ 23 ], all the MR examinations were interpreted independently by 2 board-certified radiologists with 24 years and 11 years of experience in gynecologic cancer imaging. For Rockall et al [ 25 ], all the imaging scans were read by one local and two central radiologists.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles reported on parametrial invasion ( Table 1 ) [ 6 , 21 , 22 , 23 , 24 ]. Four of these articles used parametrial invasion as a measurable outcome, and for the reference standard, three of these articles used histopathology and one used clinical examination.…”
Section: Resultsmentioning
confidence: 99%
“…We found 21 studies that investigated the use of CE-MRI in staging. Most studies compared the diagnostic accuracy of contrast and non-contrast sequences, using different types of sequences such as single-phase post-contrast acquisition [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], dynamic contrast enhancement [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and perfusion sequences [ 39 , 40 ]. These studies reported different results.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported different results. Some showed a decrease in diagnostic accuracy with the use of contrast agents [ 19 , 20 , 25 , 26 , 28 , 32 , 33 ] or did not reach statistical significance [ 10 , 23 , 24 , 27 , 31 , 36 ]. In contrast, others showed a slight improvement in diagnostic accuracy [ 15 , 17 , 21 , 22 , 29 , 30 , 34 , 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite standardized initial therapy, 10–50% of patients with cervical cancer experience recurrence ( 3 , 4 ), and the long-term survival rate for patients with recurrence is only 10–20% ( 5 ). Tumor recurrence is the leading cause of death in patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%